The sequence space lM (p, q, s) on seminormed spaces - Bekta, ÇA; Altin, Y (Indian Nat Sci Acad, 2003)
In this paper we define the sequence space l(M) (p, q, s) on a semi-normed complex linear space, by using Orlicz function and we give various properties and some inclusion relations on this space.
Keywords: Orlicz functions; sequence spaces